ANALISIS SEMANTIK TERM RIJĀL DAN NISĀ’ DALAM AL-QUR'AN: PERSPEKTIF GEOFFREY LEECH SERTA IMPLIKASINYA TERHADAP KONSEP KESETARAAN GENDER - Moh. Samsul Ma'arif; Abd Hamid; Ahmad Zaini; Taufiqurrahman Taufiqurrahman (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This paper aims to examine the meanings of the Qur’anic terms rijāl and nisā’ through the semantic perspective developed by Geoffrey Leech and to explore their implications for the concept of gender equality. The discussion focuses on identifying their lexical origins, semantic dimensions, and contextual functions in various Qur’anic verses. A descriptive qualitative method is employed to provide a comprehensive and context-oriented analysis of how these terms are utilized within the Qur’anic discourse. The findings reveal that rijāl and nisā’ do not merely denote biological categories of men and women but also convey broader social, ethical, and functional meanings depending on their textual contexts. In several verses, rijāl emphasizes responsibility, capability, and social roles, whereas nisā’ highlights aspects of womanhood, family relations, and social interaction. The semantic variations found in both terms demonstrate that the Qur’an presents gender relations through diverse linguistic expressions rather than rigid hierarchical categories. These findings suggest that interpretations of gender in the Qur’an should consider contextual and semantic nuances to avoid reductionist readings. Consequently, a semantic approach offers a valuable framework for understanding the dynamic relationship between language, meaning, and gender discourse in the Qur’an. Such an approach also contributes to a more balanced and inclusive understanding of gender equality within contemporary Islamic studies.